Education on Sorting and Managing Organic and Inorganic Waste in Sondakan Village - Titiek Puji Astuti; Nur Hidayati; Rosi Wulandari (Universitas Negeri Semarang, 2026)
This community service activity aims to provide education and assistance to Family Empowerment and Welfare (FEW) in Sondakan Village, regarding waste sorting and management, especially waste originating from households, both organic and inorganic waste. Waste sorting and management are crucial solutions for maintaining environmental cleanliness and public health. Furthermore, proper waste management can reduce the accumulation of waste in the environment. This can be the first step in sustainable and environmentally waste management in accordance with the 3R principles (Reduce, Reuse and Recycle). Through this community service program, it is hoped that the Sondakan community can implement waste sorting and management activities in their respective residences. The activity was carried out in May 2026 and was attended by representatives of FEW at Sondakan Village, using observation, presentation and interactive counseling methods, discussions, field practice and evaluation. The results of the activity showed an increase in knowledge, enthusiasm and participation of FEW in managing household waste, making composters as a medium for managing organic waste and the emergence of initiatives to form a waste bank community. This program makes a real contribution to building collective awareness of the importance of a clean environment and sustainable household-based waste management.